Cancer vaccines: current status and future directions - Yingqiong Zhou; Yuquan Wei; Xiaohe Tian; Xiawei Wei (Journal of Hematology & Oncology)
Abstract Cancer continues to be a major global health burden, with high morbidity and mortality. Building on the success of immune checkpoint inhibitors and adoptive cellular therapy, cancer vaccines have garnered significant interest, but their clinical success remains modest. Benefiting from advancements in technology, many meticulously designed cancer vaccines have shown promise, warranting further investigations to reach their full potential. Cancer vaccines hold unique benefits, particularly for patients resistant to other therapies, and they offer the ability to initiate broad and durable T cell responses. In this review, we highlight the antigen selection for cancer vaccines, introduce the immune responses induced by vaccines, and propose strategies to enhance vaccine immunogenicity. Furthermore, we summarize key features and notable clinical advances of various vaccine platforms. Lastly, we delve into the mechanisms of tumor resistance and explore the potential benefits of combining cancer vaccines with standard treatments and other immunomodulatory approaches to improve vaccine efficacy.